Interdisciplinarity in social work: integrating knowledge and practice for holistic interventions - Dughi, Tiberiu (Technium Social Sciences Journal, 2025)
In social work, interdisciplinarity is becoming more and more important in tackling difficult social problems needing several points of view and knowledge. Combining ideas from other fields improves the success of treatments by offering complete and durable answers. This paper investigates the theoretical underpinnings of interdisciplinarity in social work, the function of multidisciplinary cooperation in practice, the advantages and difficulties of this kind of approach, also with reference to policy and education in support of multidisciplinary frameworks and future directions including the influence of digital developments and artificial intelligence in interdisciplinary collaboration. Social work can enhance client results and increase its influence in tackling contemporary society issues by means of multidisciplinary collaborations.